Impact Analysis of Road Construction Projects on the Environment and Society - Victor, Shinedy Louis (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
This research explores the impact of road construction projects on the environment and society, aiming to provide a comprehensive analysis of both the direct and indirect consequences of infrastructure development. Through a detailed review of historical trends, case studies, and comparative analyses, the study highlights the significant environmental and social impacts associated with road construction. Key environmental concerns include habitat destruction, increased pollution, and noise pollution, while social impacts encompass displacement, changes in property values, and community disruption. The research reveals that while road construction projects can offer substantial benefits, such as improved connectivity and economic growth, they also pose challenges that need to be addressed. Advances in technology and methodology have enhanced our understanding of these impacts, leading to more effective mitigation strategies and better planning practices. However, the study identifies gaps in the implementation and effectiveness of Environmental and Social Impact Assessments (EIAs and SIAs) and emphasizes the need for rigorous monitoring and adaptive management. This research contributes valuable insights for policymakers, planners, and developers, guiding the creation of infrastructure that supports long-term sustainability and enhances quality of life.